Ycf48 involved in the biogenesis of the oxygen-evolving photosystem II complex is a seven-bladed beta-propeller protein - Yu, Jianfeng; Knoppová, Jana; Michoux, Franck; Bialek, Wojciech; Cota, Ernesto; Shukla, Mahendra K; Strašková, Adéla; Pascual Aznar, Guillem; Sobotka, Roman; Komenda, Josef; Murray, James W; Nixon, Peter J (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Robust photosynthesis in chloroplasts and cyanobacteria requires the participation of accessory proteins to facilitate the assembly and maintenance of the photosynthetic apparatus located within the thylakoid membranes. The highly conserved Ycf48 protein acts early in the biogenesis of the oxygen-evolving photosystem II (PSII) complex by binding to newly synthesized precursor D1 subunit and by promoting efficient association with the D2 protein to form a PSII reaction center (PSII RC) assembly intermediate. Ycf48 is also required for efficient replacement of damaged D1 during the repair of PSII. However, the structural features underpinning Ycf48 function remain unclear. Here we show that Ycf48 proteins encoded by the thermophilic cyanobacterium Thermosynechococcus elongatus and the red alga Cyanidioschyzon merolae form seven-bladed beta-propellers with the 19-aa insertion characteristic of eukaryotic Ycf48 located at the junction of blades 3 and 4. Knowledge of these structures has allowed us to identify a conserved "Arg patch" on the surface of Ycf48 that is important for binding of Ycf48 to PSII RCs but also to larger complexes, including trimeric photosystem I (PSI). Reduced accumulation of chlorophyll in the absence of Ycf48 and the association of Ycf48 with PSI provide evidence of a more wide-ranging role for Ycf48 in the biogenesis of the photosynthetic apparatus than previously thought. Copurification of Ycf48 with the cyanobacterial YidC protein insertase supports the involvement of Ycf48 during the cotranslational insertion of chlorophyll-binding apopolypeptides into the membrane.
Keywords: fotosystém I (proteinový komplex); Bacterial Proteins; bakteriální proteiny; fotosystém II (proteinový komplex); chlorophyll-binding proteins; Photosystem I Protein Complex; sinice; Cyanobacteria; photosystem II; photosynthesis; Photosystem II Protein Complex